DAYA TUMBUH TANAMAN CEMPAKA KUNING (Michelia champaca L) DENGAN MENGGUNAKAN UKURAN STEK BATANG - Raihan Salsabila; Lina Rahmawati; Kamaliah (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Ar-Raniry Banda Aceh, Indonesia, 2023)
Research on the growth potential of the Cempaka Kuning plant (Michelia champaca L) using several sizes of stem cuttings, the aim is to determine the growth potential of the Cempaka Kuning plant using several sizes and shapes of stem cuttings. This research is located in LA Garden Gampong Pango Raya, Ulee Kareng District, Banda Aceh. The parameters observed in this study were the emergence of shoots. The results showed that the Cempaka Kuning plant had a diameterof 0.5 and 1 with the highest number of shoots produced in the D2P1 treatment combination with an average value of 5.5 and the lowest number of shoots wasproduced in the D2P3 combination with an average value of 1.75.